UAV - Red Green Blue (RGB) Point Cloud (PC) from Lönnstorp UAV SAFE B 2020, 2020-04-20 - Lönnstorp Research Station (Swedish University of Agricultural Sciences, 2023)
Point cloud generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm. The points contain a value for color, from RGB photos.
Lönnstorp Research Station (2023). UAV - Red Green Blue (RGB) Point Cloud (PC) from Lönnstorp UAV SAFE B 2020, 2020-04-20 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/x1ixeScLrFkYmteNIzjFT0Ft
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap